Hard Choices : A Memoir - Clinton, Hillary Rodham (London Simon et Schuster, 2014)
Hillary Rodham Clinton's inside account of the crises, choices and challenges she faced during her four years as America's 67th Secretary of State.
Include Color Illustrations and Index.
Keywords: United States -- Clinton, Hillary Rodham -- Politics and government -- Diplomatic relations -- Cabinet officers